Relationship between students’ performance on weekly task assessments and final practical exam at the preclinical restorative dentistry course - Ayar, Muhammet Kerim (The European Research Journal, 2019)
Objectives: The purpose of this study was to examine the relationships between dental students’ performance on weekly practical task assessments, midterm practical exam and final practical exam in the preclinical restorative dentistry course. Methods: Scores of final practical exam, midterm practical exam and weekly practical task assessments in the restorative dentistry preclinical course in the half year of the third year of the curriculum at Biruni University Faculty of Dentistry were compared. It was hypothesized that students that performed highly on weekly task assessments would perform highly on the midterm and final practical exams. Results: The results showed that the weekly practical task assessment scores were correlated with the midterm practical exam and final practical exam scores and were a positive predictor. However, final practical exam scores were significantly lower than midterm practical exam and weekly practical task assessment scores. Conclusions: The quality assessments of students’ weekly tasks would be an effective predictor to assess student’s preclinical performance. Thus, it would be recommended that integrating weekly task assessment into the preclinical restorative dentistry curriculum as an effective assessment tool.